In silico analysis of anti-inflammatory and anticancer properties of bioactive compounds from Pancratium triflorum (Roxb) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Herbal remedies with medicinal properties have been utilized in Asian countries for centuries. Recently, Pancratium triflorum Roxb., also known as the forest spider lily, has captured the attention of researchers due to its potential therapeutic benefits. This plant produces white flowers and contains several important phytochemicals, including Lycorine, citrate, Gallic acid, Ellagic acid, Quercetin, and Kaempferol. Molecular docking, a computer simulation technique, has been used to identify potential drug candidates that can bind effectively to the active site of a protein. This study explored the anti-inflammatory and anticancer properties of Pancratium triflorum Roxb.'s Phyto-constituents using molecular docking with Auto dock 4.2.6. The study focused on the Vioxx-bound human Cox2 receptor and the Tyrosine kinase receptor bound to Gliteritinib. Standard ligands were used for redocking, and the Swiss ADME software was employed for bioavailability prediction to validate the findings. The results showed that Lycorine and Crinine have excellent anti-inflammatory properties, while Kaempferol and Quercetin have promising anticancer properties. Further research is necessary, but these findings suggest that Pancratium triflorum Roxb. could be a valuable addition to the medical world. However, further research is required to validate these findings, and in vivo studies are needed to confirm the efficacy and safety of these phytochemicals as potential drug candidates.